Discover oil painting easy landscape painting techniques - Pollard, Julie Gilbert 1947- (Cincinnati, Ohio North Light Books, 2015)
A complete course on painting landscapes in oils. This fun and easy guide is loaded with time-honoured methods, techniques and tutorials along with ways to tweak those ideas to suit your own painting personality. No matter what your experience (or lack of experience) you will learn how to paint beautiful works of art in no time.
Materials -- Composition -- Color theory -- Techniques -- Beginning a painting -- Painting landscapes.
Includes index.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Keywords: Landscape painting -- Technique; Painting -- Technique; Painting -- Technique; Landscape painting -- Technique; Painting -- Technique